2020
DOI: 10.3389/fimmu.2020.00950
|View full text |Cite
|
Sign up to set email alerts
|

The Gastrointestinal Helminth Heligmosomoides bakeri Suppresses Inflammation in a Model of Contact Hypersensitivity

Abstract: Helminths regulate host immune responses to ensure their own long-term survival. Numerous studies have demonstrated that these helminth-induced regulatory mechanisms can also limit host inflammatory responses in several disease models. We used the Heligmosomoides bakeri (Hb) infection model (also known as H. polygyrus or H. polygyrus bakeri in the literature) to test whether such immune regulation affects skin inflammatory responses induced by the model contact sensitiser dibutyl phthalate fluorescein isothioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Similarly, H . polygyrus also reduces the level of neutrophil‐specific chemokines in mice in a model of contact hypersensitivity 34 …”
Section: Neutrophils and Hookworm's Excretory/secretory Products: A S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, H . polygyrus also reduces the level of neutrophil‐specific chemokines in mice in a model of contact hypersensitivity 34 …”
Section: Neutrophils and Hookworm's Excretory/secretory Products: A S...mentioning
confidence: 99%
“…32,33 Similarly, H. polygyrus also reduces the level of neutrophil-specific chemokines in mice in a model of contact hypersensitivity. 34 While hookworm ES proteins have now been studied for several decades, only a few functions are fully characterized. A platelet activatingfactor(PAF)hydrolase(Table 1) was identified in adult stages of N. brasiliensisandfoundtoinhibitPAF,apotentchemoattractantof eosinophils and neutrophils.…”
Section: Hookworm Es Products Block Neutrophil Recruitmentmentioning
confidence: 99%
“…However, mice infected with the intestinal nematode Heligmosomoides polygyrus were less susceptible in a model of skin contact hypersensitivity. The mechanism is unknown but seems to be independent of Tregs [52].…”
Section: Parasites In Psoriasis -Better Than a Worse Playermentioning
confidence: 99%
“…2,3 We and others have shown that worm infection can dampen immune responses to infection and vaccination in the skin. [4][5][6] Enhanced T helper-cell type 2 (TH2) and regulatory (TREG) responses are commonly suggested to drive the down-modulating effects of worms on subsequent immune responses. 2 Furthermore, we recently described how a chronic intestinal infection with the model worm pathogen Heligmosomoides polygyrus bakerii causes redistribution of circulating lymphocytes with accumulation of T cells in the mesenteric lymph nodes (mesLNs).…”
Section: Introductionmentioning
confidence: 99%